Recursion relations for a class of generalized eliptic integrals - Glasser, M. L.; Kalla, S. L. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Our purpose in this note is to provide a number of recursión formulas for RÂµ (véase archivo PDF), so that the numerical results can be extended to arbitrary parameter values.